Identification of Human Remains by DNA Analysis of the Gastrointestinal Contents of Fly Larvae (maggots) - Waed Almegri; Nawal Mahfoud; Jalal Alshrayqi; Adel Kaweldi (AlQalam Journal of Medical and Applied Sciences, 2025)
Forensic science integrates diverse scientific disciplines to uncover facts related to unexplained events of legal significance. It is a vital component of modern investigations, involving the careful examination of physical evidence from crime scenes or suspects. Forensic biology, a key subfield, focuses on analyzing biological evidence to provide objective data that aids legal decisions and promotes justice. With ongoing scientific and technological advancements, forensic biology has emerged as crucial tool in resolving complex criminal cases. Dipteran fly larvae (maggots) are frequently collected from corpses as part of criminal investigations. Previous studies have demonstrated that DNA analysis of the gastrointestinal contents of maggots can be used to identify victims. Although this method has not yet been practically applied in criminal investigations, its practical utility remains to be validated and assessed. In a documented case, a highly decomposed body was discovered with fly larvae colonizing the facial and neck regions, rendering visual identification impossible. Short Tandem Repeat (STR) analysis was performed on the gastrointestinal contents of the collected larvae, and the resulting genetic profile was compared with that of a presumed father. The analysis revealed a paternity probability of 99%. Accordingly, the comparative DNA test enabled the accurate identification of the human remains. This case represents the first documented instance of victim identification through DNA analysis extracted from the digestive tract of larvae in a criminal investigation. The findings highlight the potential of forensic entomology in advancing forensic identification techniques and expanding its application in future criminal investigations